A study on corporate social responsibility of professional football clubs on fans’ consumption intentions in China - Zhang, Chengfeng; Song, Keke; Chen, Linhua (Frontiers in Physiology, 2025)
PurposeTo examine how Chinese fans’ perception of club CSR affects consumption intentions via fan identification and motivational attribution, and to test the moderating role of involvement.MethodsA total of 1,327 valid questionnaires were collected and analyzed using structural equation modeling and cluster analysis.ResultsCSR perception had a significant positive effect on consumption intentions; this effect was fully mediated by fan identification and motivational attribution, with the model explaining 40.3% of the variance. Highly involved fans relied primarily on the fan identification path, whereas low-involvement fans relied on the motivational attribution path.ConclusionClubs should implement differentiated CSR strategies tailored to fans’ levels of involvement to effectively enhance consumption intentions.